Estudio comparativo en gestión de la propiedad intelectual en instituciones de educación superior de India y Colombia (2014)
The present study is an analysis of intellectual property management in higher education institutions conducted in Colombia and India, whose primary objective was to develop a comparative study based on the management of intellectual property in higher education institutions ( HEIs) of such countries. This study is mainly focused on three variables that direct the research course which are awareness of intellectual property rights, attitude to intellectual property and the administration or management of intellectual property. Initially, a conceptual and literature review was conducted regarding concepts and related research with IP management, specifically related with HEIs that could contribute in the development and foundation of this research, were taken in account researches done in the same field by various universities at world. Subsequently, was done a qualitative analysis which allowed us to identify and define the purposes and goals of the investigation into what we wanted to know what took us on an exploration about regulations, management models and finally the to perform the data collection on higher education institutions of both countries, using a questionnaire as an instrument whose items were handled framed in the three aforementioned variables of interest in which is implemented Likert scales to measure each of these ones. This questionnaire was aimed at employees of higher education institutions in Colombia and India, whose nature of work were education, technical or administrative. This was done in order to study the results obtained by performing a gap analysis and comparison between the two countries. With this research is intended to promote innovation and culture to intellectual property rights IPR since it is a new topic for some institutions and still is not given the proper management and use in all HEIs.